2018
DOI: 10.1680/jgele.18.00105
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a subaqueously deposited silt iron ore tailings

Abstract: A geotechnical investigation was carried out to characterise a subaqueously deposited, primarily silt, iron ore tailings. Piezocone penetration tests (CPTu) were carried out followed by piston tube sampling at a selected target depth. Piston samples provided measures of in situ density (by means of gravimetric water content), and supplied material for reconstituted and intact laboratory testing. Reconstituted samples prepared using moist tamping (MT) for determination of the critical state locus (CSL), along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Finally, the use of moist tamping requires acknowledgement as a limitation -given that this sample preparation method has received considerable criticism, generally related to (a) non-uniformity of initial specimen void ratio (Vaid et al 1999;Daliri et al 2015), and (b) producing fabric and/or densities inconsistent with intact specimen behaviour (Vaid and Sivathayalan 2001;Daliri et al 2015) -despite the fact that, for predominately silt tailings, no sample preparation method has yet been shown to clearly produce the same shearing response compared to intact specimens of the same material (Høeg et al 2000;Chang et al 2011). Alternatively, it also suggested that the observation in this paper of in situ states looser than can be achieved with any sample preparation method, including moist tamping, for Sample C -a similar issue demonstrated in other studies (Fourie and Papageorgiou 2001;Shuttle and Cunning 2007;Reid et al 2018b) -is an additional factor that should be considered in the context of the suitability of different preparation techniques to simulate in situ behaviour.…”
Section: Limitationssupporting
confidence: 57%
See 2 more Smart Citations
“…Finally, the use of moist tamping requires acknowledgement as a limitation -given that this sample preparation method has received considerable criticism, generally related to (a) non-uniformity of initial specimen void ratio (Vaid et al 1999;Daliri et al 2015), and (b) producing fabric and/or densities inconsistent with intact specimen behaviour (Vaid and Sivathayalan 2001;Daliri et al 2015) -despite the fact that, for predominately silt tailings, no sample preparation method has yet been shown to clearly produce the same shearing response compared to intact specimens of the same material (Høeg et al 2000;Chang et al 2011). Alternatively, it also suggested that the observation in this paper of in situ states looser than can be achieved with any sample preparation method, including moist tamping, for Sample C -a similar issue demonstrated in other studies (Fourie and Papageorgiou 2001;Shuttle and Cunning 2007;Reid et al 2018b) -is an additional factor that should be considered in the context of the suitability of different preparation techniques to simulate in situ behaviour.…”
Section: Limitationssupporting
confidence: 57%
“…The sample was also likely exposed to less subsequent drying than the other samples, which is consistent with the lower TDS for this sample. Difficulties preparing silty tailings to densities as loose as those observed in situ have been previously observed (Cunning and Jefferies 2004;Shuttle and Cunning 2007;Reid et al 2018b), and the different states generally resulting from subaerial and subaqueous deposition have previously been noted (Reid and Jefferies 2017). The reasons for this observed behaviour are not fully clear -although the effects of the pluviation of soils through "dirty" water has been suggested as a potential contributing factor (Vaughn 1997).…”
Section: Comparison To In Situ Statementioning
confidence: 72%
See 1 more Smart Citation
“…As such, their deposition would be subaqueous. There is increasing evidence that silty tailings subaqueous deposited achieved looser states than those deposited subaerially on a tailings beach (Reid et al 2018;Reid & Jefferies 2017). Indeed, a similar comparison to the one carried out herein on a subaqueously deposited conventional tailings indicated similarly loose states that could not be replicated in the laboratory (Reid et al 2018) -with detailed gradation testing indicating the loose state was not a result of segregation within the in situ specimens.…”
Section: Discussion Of Slurry-preparation Methodsmentioning
confidence: 99%
“…Hence, the CSL is the condition in which the soil deforms under constant volume and stable mean effective stress. The CSL is widely applied for flow liquefaction assessment [3][4][5], stress-dilatancy analyses [6][7][8] and characterisation of mine tailings [9][10][11][12]. The conventional triaxial test is commonly used for determining the CSL in the three-dimensional invariant space of shear-confinement-volume state, that is, a representation in the e : p : q space.…”
Section: Introductionmentioning
confidence: 99%